PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KOMPETENSI INTERPERSONAL SISWA KELAS X IIS SMA NEGERI 12 PEKANBARU - Yuniarti, Mella Yuniarti; Umari, Tri Umari; Arlizon, Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the effect of group counseling services for interpersonal competence improvement high school students in class X IIS N 12 Pekanbaru. The method used was experimental method. The collect the data used total sampling technique. The subject were high school students in class X IIS N Pekanbaru were 30 students. Before have guidance services group all interpersonal competence stundents competence is category is medium. In the process of guidance services group to improve progress in the interpersonal competence every meeting. The result showed that group counseling can improve the interpersonal competence of students. This is evident from analysis the value of is greater than t table with a significant level ofÂ  5% (7,5>2,000). Than Ho rejected and Ha accepted,which means there is a significant difference to the improvement of interpersonal competence of students before given after the guidance services group. Interpersonal competence students is better after has guidance services group than before guidance services group. Guidance services group give positive effect improve to interpersonal competence. The technique to get data in the research using by only instrument and observation,the next researcher suggestion to add technique to get accurate data. To the next researcher can do reseach by the other aspect of interpersonal competence. Key Words: Guidance Services Group,Interpersonal Competence.